Transformations in the International System after the Ukrainian War: The End of Unipolarity and the Rise of Multipolarity - Tariq Kakarash Muhyiddin (International Journal of Law Research and Studies, 2025)
The international system after the Ukraine war has undergone profound changes, marking the decline of U.S.-led unipolarity since the Cold War. Russia and China have emerged as balancing powers, supported by alliances such as BRICS and the Shanghai Cooperation Organization. Strategic rivalry among major powers has reshaped global relations toward emerging multipolarity. Traditional institutions like the UN and Bretton Woods’s bodies have lost effectiveness in addressing successive crises. The war deepened the East-West divide and accelerated Europe’s remilitarization. Meanwhile, regional powers such as India, Turkey, and Iran have risen as influential actors. Economic sanctions have pushed states to seek alternatives to the Western-dominated financial system. Energy and food have become tools of geopolitical leverage. These dynamics signal a more complex and competitive world order. Ultimately, the war represents the beginning of a multipolar system whose final shape is still unfolding.
Keywords: International System; Ukrainian War; Unipolarity; Multipolarity